Pengaruh Rizobakteria Pemacu Tumbuh dan Toleran Kekeringan serta Kelimpahan dan Akitvitas Mikroba Tanah terhadap Tanaman Jagung (Zea mays L.) - Hari KAPLI; Aris Tri WAHYUDI; Edi HUSEN (Universitas Jambi, 2017)
Agricultural land in Indonesia was largely dominated by untapped potential land, almost of that potential land is dry land. Maize (Zea mays L.) is one of the staple crops that are known could be cultivated on dry land. Rizosphere has been known to containmicroorganisms that can improve the plant growth. In the previously study, we have screenedin vitro of rhizobacteria (6 isolates of Pseudomonas sp CRB and 7 isolates of Bacillus sp CR) as growth promoter of maize and drought tolerant. A total of 6 rhizobacterial formula were further applied in vivo in greenhouse to promote the growth of maize. In planta test on maize showed that formula CRB 19 and F3 (CR 83 + CRB 10) were the best formula that could enhance plant growth parameters under drought stress conditions. After that abundance and activities of microbe were analyzed by enumeration of total fungus, bacteria and actinomycetes, dehidrogease test, soil respiration test dan C-microbe test and those tests showed that formula CRB 19 and F3 (CR 83 + CRB 10) were the best formula.These formula could be recommended as inoculants of maize planted in dry land agriculture. Keywords : drought tolerant,formulation, growth promoter, maize, rhizobacteria